PERMIAN STRATIGRAPHY IN THE NORTHERN KARAKORUM, PAKISTAN (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1995)
The stratigraphical data collected during four geological expeditions to the Northern Karakorum (1996,1991,1992a,1992b) are discussed. The sedimentary succession has been classified by 9 formations, here formalised, and subdivided into members and lithozones. The biochronology has been established on fusulinids, brachiopods, and conodonts. Several plates illustrate the most significant fossil species as well as the litho- and microfacies. The sedimentary succession may be roughly subdivided into three parts. The lower part consists of terrigenous rocks, mostly pelitic and less frequently arenaceous(quartzarenites with thick arkose intervals during the latest  Asselian-early Sakmarian). They are evidence of a continental to coxtal environment, with short term marine  ingressions. The second part begins with the Sakmarian, when the marine environment spread over most of the studied area. Bioclastic sand bars with brachiopods and crinoids at the base are followed by huge fusulinid packages. In Hunza oolitic bars and dolostone peritidal cycles also follow. The carbonate ramp is often polluted by terrigenous sediments, especially westwards. Temporary arenaceous spillovers (quartzarenites), often linked to minor  sedimentation gaps, occur both westwards in the Baroghil area, and eastwards in the Hunza-Shimshal area. In the centre, in the Upper  Karambar valley, a large gap most probably occurs, with reappearance of the sedimentation only with the dolostones of the Upper Permian. These erosional episodes with arenaceous spillovers are interpreted as being linked to rifting events of the Neotethys opening, active  southwards. The third part of rhe succession concerns the Late Permian. Towards the end at the Murgabian or at the beginning of the Midian, the Northern  Karakorum is subdivided into two major areas. To the west, after a transgressive episode with ironstone deposition, a wide peritidal carbonate platform spread over from Baroghil to Chillinji in Karambar and the Pasu area in Hunza. This palaeogeographic pattern extends up to the Triassic. However, biostratigraphic control is poor. Instead to the north-east, a progressive sinking of the slope is observed,  with spreading of deeper environments and cherty limestone deposition. The down-warping is activated by block-faulting resulting in huge megabreccia bodies interbedded with the cherty limestones. During the Dzhulfian, significant clay inputs dilute the carbonate mud accumulation and shales are dominant around the Permian-Triassic boundary. Pelagic carbonate sedimentation gradually recovers from the Smithian onward. The Permian of the Karakorum is the sedimentary evidence of the passive margin of a lithospheric block, detached from the Gondwana continent during the Permian, that will later migrate towards the centre  of the Paleo-Tethys, along with other lithospheric blocks of the Mega Lhasa plate.
Keywords: Permian; Stratigraphy; Foraminifera; Coelenterata; Brachiopoda; Bivalvia; Conodonta; Sandstone petrography; Microfacies; Paleogeography; Karakorum; Pakistan.